Hubungan Efikasi Diri Dengan Prokrastinasi Akademik Pada Mahasiswa - Wahyuningsih, Puput; Rahmawati; Handoyo, Alfandy Warih (SISTEMA: Jurnal Pendidikan, 2021)
This study aims to determine the relationship between self-efficacy and academic procrastination in students. The research population is the sixth semester students of the Faculty of Teacher Training and Education, Sultan Ageng Tirtayasa University. The sampling technique used random sampling with the Solvin formula which resulted in a sample of 294 students. Data analysis using regression analysis and correlation using SPSS 21 for windows. Correlation test results obtained R = -0,513, p = 0,000 (p <0,05). So it can be concluded that the self-efficacy variable has a significant negative relationship with academic procrastination. The effect of self-efficacy on academic procrastination seen from the results of the coefficient of determination (R = 0,264) shows the effective contribution given by the self-efficacy variable to academic procrastination by 26,4%. Therefore, there are still 73,6% of other factors outside the study that may cause academic procrastination behavior in students.